2023
DOI: 10.1039/d3cc02948d
|View full text |Cite
|
Sign up to set email alerts
|

Constructing single atom sites on bipyridine covalent organic frameworks for selective electrochemical production of H2O2

Abstract: We developed a series of single atom catalysts (SACs) anchored on bipyridine-rich COFs. By tuning the active metal center, the optimal Py-Bpy-COF-Zn shows the highest selectivity of 99.1% and excellent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…This is because the introduction of oxygen functional groups can significantly change the surface properties and charge distribution of the carbon materials, thereby adjusting the adsorption characteristic of HOO* on the material surface and promoting the occurrence of the 2e − ORR. 26 In this study, the oxygen content of the carbon substrate increased from 0.91% (Ni–N/C) to 14.36% (Ni–N/C ox ) after oxidation with concentrated nitric acid, and its 2e − ORR activity was also enhanced accordingly (Fig. 1a), confirming the effectiveness of O doping in improving the catalytic performance of carbon materials.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…This is because the introduction of oxygen functional groups can significantly change the surface properties and charge distribution of the carbon materials, thereby adjusting the adsorption characteristic of HOO* on the material surface and promoting the occurrence of the 2e − ORR. 26 In this study, the oxygen content of the carbon substrate increased from 0.91% (Ni–N/C) to 14.36% (Ni–N/C ox ) after oxidation with concentrated nitric acid, and its 2e − ORR activity was also enhanced accordingly (Fig. 1a), confirming the effectiveness of O doping in improving the catalytic performance of carbon materials.…”
Section: Resultssupporting
confidence: 68%
“…Density functional theory calculations demonstrated that the stronger electronegative O atom results in the d-band center of the transition metal atoms shifting toward a lower energy, thus strengthening the adsorption of O 2 and weakening the adsorption of OOH*, which favors the 2e − ORR pathway. 26 Although fruitful results have been achieved in this area, research on SACs with the M–N 4− x O x configuration needs to be further deepened, and the influence of the synergistic effect of multiple active centers cannot be ignored. Therefore, there is still room for improvement in developing more efficient SACs, and the exploration will provide valuable insights and promising catalysts design, driving the development of greener and more efficient H 2 O 2 production methods.…”
mentioning
confidence: 99%
“…Huang et al anchored a series of SACs on bipyridine-rich COFs (Py-Bpy-COF-M, where M is Mn, Fe, Co, Ni, Cu, or Zn). 147 Despite Zn displaying low ORR activity, it catalyzed H 2 O 2 with the highest selectivity at 9.278 mol g catalyst −1 h −1 . They attribute the performance to a relatively high *OOH dissociation barrier.…”
Section: Cof-based Sacs For Electrocatalytic Energy Applicationsmentioning
confidence: 99%
“…In addition, the activation energy barrier and dissociation energy barrier of *OOH are critical for H 2 O 2 selectivity. Huang et al anchored a series of SACs on bipyridine-rich COFs (Py-Bpy-COF-M, where M is Mn, Fe, Co, Ni, Cu, or Zn) . Despite Zn displaying low ORR activity, it catalyzed H 2 O 2 with the highest selectivity at 9.278 mol g catalyst –1 h –1 .…”
Section: Cof-based Sacs For Electrocatalytic Energy Applicationsmentioning
confidence: 99%
“…Owing to the intuitive structural and chemical modularity afforded by metal–ligand coordination and covalent bonding, metal–organic (MOFs) and covalent organic frameworks (COFs) are the most well-studied and well-developed classes of synthetic porous frameworks. 1,2 Although constructing low-density structures through noncovalent interactions is considered an unreliable enterprise by many, considerable advancements have indeed been made with hydrogen-bonded (H-bonded) organic frameworks (HOFs). 3,4 Among the canonical noncovalent interactions, the preferred directionality and strength of H-bonding enables assembly of interaction motifs (synthons) between molecular building blocks (tectons).…”
mentioning
confidence: 99%